2005
DOI: 10.3171/spi.2005.3.1.0017
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study investigating the postoperative progression of ossification of the posterior longitudinal ligament in the cervical spine: a new computer-assisted measurement

Abstract: Object. Ossification of the posterior longitudinal ligament (OPLL) often progresses after surgery, and this may cause late-onset neurological deterioration. There have been few studies, however, to clarify any correlation between progression and clinical outcome, partly because of the lack of studies involving reliable and reproducible methods by which detection of progression is made possible. The authors conducted a multicenter study to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
73
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 11 publications
4
73
1
Order By: Relevance
“…They found that progression was marked in younger patients with continuous-or mixed-type OPLL, consistent with the results of Chiba et al 12 According to progression on the longitudinal axis, the patients with continuous-or mixed-type OPLL were classified according to age. The patients 40-49 years of age showed peak progression at greater than 1 year, whereas the patients older than 50 showed peak progression during the first year of follow-up.…”
Section: Natural Historysupporting
confidence: 79%
See 1 more Smart Citation
“…They found that progression was marked in younger patients with continuous-or mixed-type OPLL, consistent with the results of Chiba et al 12 According to progression on the longitudinal axis, the patients with continuous-or mixed-type OPLL were classified according to age. The patients 40-49 years of age showed peak progression at greater than 1 year, whereas the patients older than 50 showed peak progression during the first year of follow-up.…”
Section: Natural Historysupporting
confidence: 79%
“…The rate of OPLL progression was 56.5% at 2 years and was more common in younger patients with continuous-and mixed-type OPLL. 12 Murakami et al 89 reported a case of cervical OPLL in a 67-year-old man with more than 26 years follow-up. They found that the rate of OPLL progression varied during this period.…”
Section: Natural Historymentioning
confidence: 99%
“…The next step is to analyze the risk factors for OPLL progression using our novel method, to verify those that have been described in previous studies [6,17].…”
Section: Discussionmentioning
confidence: 75%
“…Chiba et al [6,7] reported the incidence of ossification progression based on computer analysis of X-ray images in patients who had undergone laminoplasty. Measurements of ossification length and thickness using 2D X-ray images are possible to a certain extent [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation